The Measurement and Conceptualization of Coping Responses in Pediatric Chronic Pain Populations: A Scoping Review - Nabbijohn, A. Natisha; Tomlinson, Rachel M.; Lee, Soeun; Morrongiello, Barbara A.; McMurtry, C. Meghan (Frontiers in Psychology, 2021)
Background: Pediatric chronic pain is a prevalent condition that requires significant coping to encourage optimal functioning; however, relevant research is vast, heterogeneous, and difficult to interpret. To date, no attempt has been made to map and summarize the measurement and conceptualization of coping responses in the context of pediatric chronic pain. Objectives: A scoping review was conducted to map and summarize the participant characteristics, methodologies, theoretical frameworks, and measures used to assess coping responses in youth with chronic pain. The extent to which authors used definitions and examples of coping responses (conceptual clarity) as well as consistently used measures (measurement consistency) and their corresponding conceptualizations (conceptual consistency) relative to how they were intended to be used was assessed. Methods: Searches were conducted through MEDLINE (PubMed) and PsycINFO. Following title/abstract screening, full-text extractions were performed on 125 English-language publications on coping in youth with chronic pain. Results: Of the 125 studies, only 12.8% used a theoretical framework to explain the coping responses assessed and even fewer (7.2%) used theory to guide measure selection. Conceptual clarity was rated “low/very low” (i.e., no definitions and/or examples) for 47.2% of studies. The majority of studies were conducted in the United States (67%) and a preponderance of White and female participants was sampled. The research primarily used quantitative methods (85%) and cross-sectional designs (67%). Parent- or self-report questionnaires were the most common methods for assessing coping (86%). Of the 95 studies that utilized one of the 14 questionnaires with known psychometric properties, 33.7% and 55.8% had one or more discrepancies for conceptual and measurement consistency, respectively. Conclusions: This review highlights the lack of clear descriptions and theoretical frameworks of coping responses for pediatric chronic pain. Inconsistencies in the measurement and conceptualization of coping responses limit research and clinical advancements. As a field, we need to strive towards using well-developed theory to create fewer, more well-established standardized measures with clearly defined coping responses. Opportunities for qualitative and observational research in more diverse patient populations should be considered for theory construction and measure validation.